2016
DOI: 10.1051/matecconf/20179001025
|View full text |Cite
|
Sign up to set email alerts
|

Identification of damage based on frequency response function (FRF) data

Abstract: Abstract. Mechanical joints, particularly fasteners such as bolted joints have a complex non-linear behaviour. The non-linearity might emerge from the material, geometry or by the contacts in the joints. However, damage to a structure can be happened either their connections or the material of components. The effect of damage can change the dynamic properties of the structure such as natural frequencies and mode shapes and structural performance and can cause premature failure to structure. This paper presents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 11 publications
0
6
0
2
Order By: Relevance
“…Funkcja przejścia opisuje relację pomiędzy wymuszeniem a rejestrowaną odpowiedzią konstrukcji [2]. Możliwość wykorzystania funkcji przejścia do detekcji uszkodzeń została zaprezentowana między innymi w [3], [4], [5] i [6]. W [3] funkcję przejścia potraktowano jako sygnał.…”
Section: Wprowadzenieunclassified
See 1 more Smart Citation
“…Funkcja przejścia opisuje relację pomiędzy wymuszeniem a rejestrowaną odpowiedzią konstrukcji [2]. Możliwość wykorzystania funkcji przejścia do detekcji uszkodzeń została zaprezentowana między innymi w [3], [4], [5] i [6]. W [3] funkcję przejścia potraktowano jako sygnał.…”
Section: Wprowadzenieunclassified
“…Przeprowadzony eksperyment bazował niestety wyłącznie na danych numerycznych. Nieco inne podejście zaproponowano w pracy [4], gdzie wykazano, że wystąpienie uszkodzenia w układzie powoduje przesunięcie wykresu funkcji w stronę niższych częstotliwości, a ocena, czy uszkodzenie wystąpiło czy nie możliwa jest poprzez wizualne porównanie funkcji dla układu wzorcowego i uszkodzonego. W pracy [5] pokazano skuteczność detekcji uszkodzeń na rzeczywistym obiekcie (most), a w [6] wykorzystano FRF do identyfikacji uszkodzenia w postaci zmiany sztywności połączeń.…”
Section: Wprowadzenieunclassified
“…The use of the frequency response function (FRF) for damage detection and structural health monitoring has been widespread [8][9][10]. Recently, the use of FRF has been augmented by using artificial neural networks (ANN) and genetic algorithms (GA) for damage detection [11][12][13]. It has been specifically observed that ANN could be used for the detection of nonlinear damage with a high level of accuracy [11]; however, most of the techniques that use ANN require a large amount of training data.…”
Section: Introductionmentioning
confidence: 99%
“…However, this approach is not ready to be applied in field tests since high measurement accuracy is required but is difficult to be obtained in real-life structure measurements. The article [9] shows the impact of loosening connectors in the Frequency Response Function (FRF), which changes not only its shape but also decreases the resonance frequencies values. The publication also highlights the complex non-linear nature of bolted connections.…”
Section: Introductionmentioning
confidence: 99%